Neutralizing Antibody Responses to SARS-CoV-2 in Recovered COVID-19 Patients Are Variable and Correlate With Disease Severity and Receptor-Binding Domain Recognition - Maciola, Agnieszka Katarzyna; La Raja, Massimo; Pacenti, Monia; Salata, Cristiano; De Silvestro, Giustina; Rosato, Antonio; Pasqual, Giulia (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) caused outbreaks of the pandemic starting from the end of 2019 and, despite ongoing vaccination campaigns, still influences health services and economic factors globally. Understanding immune protection elicited by natural infection is of critical importance for public health policy. This knowledge is instrumental to set scientific parameters for the release of “immunity pass” adopted with different criteria across Europe and other countries and to provide guidelines for the vaccination of COVID-19 recovered patients. Here, we characterized the humoral response triggered by SARS-CoV-2 natural infection by analyzing serum samples from 94 COVID-19 convalescent patients with three serological platforms, including live virus neutralization, pseudovirus neutralization, and ELISA. We found that neutralization potency varies greatly across individuals, is significantly higher in severe patients compared with mild ones, and correlates with both Spike and receptor-binding domain (RBD) recognition. We also show that RBD-targeting antibodies consistently represent only a modest proportion of Spike-specific IgG, suggesting broad specificity of the humoral response in naturally infected individuals. Collectively, this study contributes to the characterization of the humoral immune response in the context of natural SARS-CoV-2 infection, highlighting its variability in terms of neutralization activity, with implications for immune protection in COVID-19 recovered patients.